Blogging, Twitter and journalism - Bradshaw, Paul (Henry Stewart Talks, 2010)
How blogging differs from other journalism platforms, Key developments in journalism blogging history, What makes a successful blog, What is Twitter and how is it useful for journalists and publishers?, Why RSS is central to blogging and Twitter and how it works
Archived at 2022/04/12